DIMENSIONS OF MEASURING FINANCIAL CAPABILITY: A REVIEW - Basumatary, Japil; Chanu, Ayekpam Ibemcha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Financial Capability includes both ‘Financial Literacy’ and ‘Financial Inclusion’. Financial Literacy refers to an individual's capacity to make decisions in their optimal financial interest, while Financial Inclusion refers to the opportunity of individuals to utilize this capacity to act in their best financial interest. Numerous research on financial capabilities has been done from a variety of angles. The present review study is an attempt to identify the dimensions of measuring financial capability adopted in the existing studies. The study found two distinct sets of dimensions: the Normative/ Cognitive Approach and the Positive/ Agnostic Approach. The present study attempts to introduce a new framework for measuring financial capability adopting the dimensions identified from the literature.